A wearable skin stretch device for haptic feedback - Bark, K.; Wheeler, J.; Lee, G.; Savall, J.; Cutkosky, M. (2009 World Haptics Conference, 2009)
We describe a wearable haptic feedback device that imparts rotational skin stretch to provide feedback regarding movement of a virtual object. Applications for this device include feedback of motion for physical therapy or rehabilitation exercises or proprioceptive feedback for amputees. The device uses a small piezoelectric motor for a combination of low weight, moderate torques and rotation without vibrations that could interfere with the sensation of stretch. We present the results of experiments to determine the accuracy with which subjects can use feedback from the device to control the orientation of a virtual object. Most subjects were able to position the device within several degrees. In a second test, subjects were asked to identify randomly applied levels of skin stretch while they remained passive. In this case, the accuracy was poorer and subjects occasionally confused positive and negative rotations. Tests were also conducted to evaluate the effect of rotational compliance at the end effector, added to improve comfort at large displacements.